HAVANA CONFERENCE 2006 : INDIA’S ROLE - Kumar, Vinod (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper evaluates the Havana Summit of the Non-Aligned Movement. India’s role in the Non-Aligned Movement is assessed through this summit. This summit primarily represented a strong response to unipolar globalism. Havana was lavishly decorated for this grand event. This was the second time this country, with a population of 12 million, hosted this prestigious summit. The first Havana Summit was held in 1979. During this summit, the Cold War was at its peak. Movements against colonialism and imperialism were beginning to emerge; countries like Angola and Mozambique had gained independence. Fidel Castro sparked controversy in his speech at the United Nations by describing the former Soviet Union as a "natural partner" of the Non-Aligned Movement. However, circumstances have changed dramatically since then, although Fidel Castro remained steadfast in his ideological convictions and worldview until his final moments. However, on medical advice, he decided not to attend the 2006 Havana Summit and preferred to monitor the conference proceedings from his room at the Cuban Communist Party headquarters. During this time, he was recuperating from surgery. Regarding India’s role, it played a significant and restrained role at the summit. Instead of harsh rhetoric, Indian delegates agreed to the final declaration approved by all heads of state and government.